2018
DOI: 10.1038/s41561-018-0156-y
|View full text |Cite
|
Sign up to set email alerts
|

Current level and rate of warming determine emissions budgets under ambitious mitigation

Abstract: Some of the differences between recent estimates of the remaining budget of carbon dioxide (CO 2) emissions consistent with limiting warming to 1.5°C arise from different estimates of the level of warming to date relative to pre-industrial conditions, but not all. Here we show that, for simple geometrical reasons, the combination of both the level and rate of human-induced warming provides a remarkably accurate prediction of remaining emission budgets to peak warming across a broad range of scenarios, if budge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 38 publications
3
30
0
1
Order By: Relevance
“…Lastly, we wanted to explore the impact of assuming proportionality between CO 2 induced forcing to net non-CO 2 forcing. This is an assumption, made by several recent studies 9,10 , of a constant future ratio between the net non-CO 2 forcing and the CO 2 induced forcing. For this implementation, we used the observed ratio of the net non-CO 2 forcing to the total CO 2 forcing for the 20 years period from 1995 to 2015, which gives a value of 0.26.…”
Section: Non-co 2 Forcing Scenariosmentioning
confidence: 97%
See 1 more Smart Citation
“…Lastly, we wanted to explore the impact of assuming proportionality between CO 2 induced forcing to net non-CO 2 forcing. This is an assumption, made by several recent studies 9,10 , of a constant future ratio between the net non-CO 2 forcing and the CO 2 induced forcing. For this implementation, we used the observed ratio of the net non-CO 2 forcing to the total CO 2 forcing for the 20 years period from 1995 to 2015, which gives a value of 0.26.…”
Section: Non-co 2 Forcing Scenariosmentioning
confidence: 97%
“…In a recent overview of studies assessing the 1.5°C carbon budget, Rogelj et al 8 showed that 9 out of 14 studies did not use non-CO 2 warming that is consistent with the assumed net-zero CO 2 emissions pathway. This includes some analyses that assumed a proportionality of future CO 2 and non-CO 2 forcing (i.e., that the relative contribution to future warming from non-CO 2 emission remains similar to today) 9,10 , as well as others who prescribed non-CO 2 forcing from one or more representative concentration pathway (RCP) scenarios [11][12][13] . Both approaches are problematic.…”
Section: Introductionmentioning
confidence: 99%
“…The current GHG emission rate, if it persists, will result in continuation of the current rate of global temperature increase of ~0.2°C per decade (e.g. Haustein et al 2017), crossing the 1.5°C Paris Agreement target by the 2040s (Leach et al 2018).…”
Section: Climate Changementioning
confidence: 99%
“…5 o C becomes 'likely'. For example, Leach et al[11] introduced a new metric-an 'adaptation/mitigation timescale'-to capture this thinking, i.e. calculating the remaining time until a given temperature target is exceeded if the current rate of warming continues.…”
mentioning
confidence: 99%
“…calculating the remaining time until a given temperature target is exceeded if the current rate of warming continues. Instead of inferring from carbon budgets estimated by model simulations, Leach et al[11] used observational data alone, an approach claimed to be more scientifically rigorousthan relying on models (see also ref. 12).…”
mentioning
confidence: 99%